Lateral Thinking According to Brain Dominance Patterns and its Relationship to the Accuracy of Complex Skill Performance Among Football Students - Ali Ayoob Younus (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
This study aimed to examine the relationship between brain dominance tendencies and an individual’s creative thinking ability, as well as its impact on high level performance in football. The participants consisted of 59 third year students from the College of Physical Education and Sports Sciences at the University of Samarra. A descriptive research design with a correlational approach was employed. All participants were assessed using the Torrance Brain Dominance Scale to classify them into three categories: right-brain dominant (22 students), left-brain dominant (19 students), and integrated (both right and left-brain dominant) (18 students). Lateral thinking ability was measured using the Lateral Thinking Scale developed by Al-Qazwini. In addition, four performance tests previously developed and standardized for the same sample were used to assess skill performance. The results revealed a statistically significant negative (inverse) correlation between lateral thinking ability and final skill performance across all brain dominance patterns. The integrated group demonstrated the best performance, with a mean lateral thinking score of 16.4 and an average performance time of 59.8 seconds. This group also showed the strongest negative correlation coefficient (r = -0.63; p = 0.006). In contrast, the left-brain dominant group exhibited the weakest correlation (r = -0.38). Based on these findings, it can be concluded that integrated brain dominance enhances an individual’s ability to process complex skills. This advantage is reflected in faster response times, greater accuracy, and improved execution of innovative actions under test conditions, resulting from the effective integration of both left and right brain functions.